Fuelling war : natural resources and armed conflict - Le Billon, Philippe; International Institute for Strategic Studies (Abingdon, Oxon ; New York : Routledge for the International Institute for Strategic Studies, London, 2005)
A generous endowment of natural resources should favour rapid economic and social development. The experience of countries like Angola and Iraq, however, suggests that resource wealth often proves a curse rather than a blessing. Billions of dollars from resource exploitation benefit repressive regimes and rebel groups, at a massive cost for local populations. This Adelphi Paper analyses the economic and political vulnerability of resource-dependent countries; assesses how resources influence the likelihood and course of conflicts; and discusses current initiatives to improve resource governance in the interest of peace. It concludes that long-term stability in resource-exporting regions will depend on their developmental outcomes, and calls for a broad reform agenda prioritising the basic needs and security of local populations.
The resource curse. Iraq and the resource curse ; The collapse of economic growth ; Governance failure ; Resources, governance failure and identity in Nigeria ; Conflicts and violence -- Resources and armed conflicts. War and resource accessibility ; Resources and types of armed conflicts ; Influencing the course of armed conflicts -- Implications for conflict prevention and termination. Addressing the resource curse ; Ending resource wars ; Increasing corporate responsibility ; Regulating conflict diamonds.
Includes bibliographical references (p. [85]-92).
Keywords: Natural resources; War -- Economic aspects; Resource curse